2022
DOI: 10.3390/ijms232415938
|View full text |Cite
|
Sign up to set email alerts
|

Voglibose Regulates the Secretion of GLP-1 Accompanied by Amelioration of Ileal Inflammatory Damage and Endoplasmic Reticulum Stress in Diabetic KKAy Mice

Abstract: Voglibose is an α-glycosidase inhibitor that improves postprandial hyperglycemia and increases glucagon-like peptide-1 (GLP-1) secretion in patients with type 2 diabetes. Recently, there has been increasing interest in the anti-inflammatory effects of voglibose on the intestine, but the underlying mechanism is not clear. This study evaluated the effects and mechanisms of voglibose on glycemic control and intestinal inflammation. Type 2 diabetic KKAy mice were treated with voglibose (1 mg/kg) by oral gavage onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Currently, the role of the inflammatory response in promoting the pathological processes in T2DM and its impact on affected tissues and organs is well recognized. Several studies have provided insights into the mechanisms by which T2DM induces inflammation and oxidative stress. It is indisputably beneficial to modulate the inflammatory response in T2DM patients. The cardiovascular, renal, and other organ-protective effects of novel antidiabetic medications have been attributed to their anti-inflammatory properties . Colonic inflammation, with its detrimental effects on the mucosal barrier, bacterial infection, and insulin resistance, has been implicated in various diseases, including diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the role of the inflammatory response in promoting the pathological processes in T2DM and its impact on affected tissues and organs is well recognized. Several studies have provided insights into the mechanisms by which T2DM induces inflammation and oxidative stress. It is indisputably beneficial to modulate the inflammatory response in T2DM patients. The cardiovascular, renal, and other organ-protective effects of novel antidiabetic medications have been attributed to their anti-inflammatory properties . Colonic inflammation, with its detrimental effects on the mucosal barrier, bacterial infection, and insulin resistance, has been implicated in various diseases, including diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 21 25 The cardiovascular, renal, and other organ-protective effects of novel antidiabetic medications have been attributed to their anti-inflammatory properties. 26 Colonic inflammation, with its detrimental effects on the mucosal barrier, bacterial infection, and insulin resistance, has been implicated in various diseases, including diabetes. A growing body of evidence has shown an association between the development of T2DM and its complications with a state of chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that inflammatory response and increased oxidative stress may be crucial factors in the development of T2DM [ 7 , 8 ]. Intestinal inflammatory damage is one of the metabolic disorders induced by diabetes [ 9 ]. Many studies have demonstrated that patients with type 2 diabetes are accompanied by disturbances of the intestinal microbiota and disruption of intestinal permeability, which can cause damage to multiple organs and lead to a number of complications [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%